Initiation of quarterly palmitate paliperidone in French clinical practice: Results from the observational, cross‐sectional OPTIMUS study. Issue 3 (6th January 2022) - Gary, Charlotte; Déal, Cécile; Boursicot‐Beuzelin, Jennifer; Falissard, Bruno; Giordana, Jean‐Yves; Fakra, Eric; Samalin, Ludovic; Bouju, Sophie
Abstract: Purpose: Long‐term antipsychotic treatment is key to a positive clinical outcome in schizophrenia. Recent guidelines recommend the prescription of long‐acting antipsychotic formulations (LAIs) as early as the first episode in patients with schizophrenia. The OPTIMUS study evaluated real‐world use of a new three‐monthly paliperidone palmitate formulation (PP3M) in France. Methods: For this observational cross‐sectional study, all French psychiatrists were invited to enrol patients who had initiated PP3M in the previous 4 months. Snapshot data were collected at a routine consultation, without any modification of clinical practice. Results: This population of 350 patients with schizophrenia started on PP3M predominantly included single men, living independently with a diagnosis of schizophrenia for a median of 9.3 years. Demographic characteristics were broadly comparable to those reported in other studies on LAIs. Investigators cited treatment simplification (96.9%) and patient comfort (93.3%) as the most common reasons for switching to PP3M; enhancing adherence was mentioned less often (61.1%) with most patients previously considered as adherent, and a majority of them expressing a positive attitude to their treatment. One‐third of patients accepted the psychiatrist's proposal to initiate PP3M treatment without any discussion, and relatives were involved in the therapeutic decision‐making process in only 23.7% of cases. After initiation, few changes were seen in professional follow‐up frequency or concomitant pharmacological and non‐pharmacological treatment modalities except for a decrease in antipsychotic polytherapy. Conclusions: PP3M is mostly prescribed in adherent patients with fairly stable schizophrenia, and the longer dosing interval does not substantially affect patient care.